2012
DOI: 10.1016/j.jacc.2012.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Electrophysiological Study in a 3-Dimensional Cardiac Magnetic Resonance Imaging Model of Porcine Myocardial Infarction

Abstract: Objective This study sought to test the hypothesis that “virtual” electrophysiologic studies (EPS) on an anatomic platform generated by 3D MRI reconstruction of the left ventricle (LV) can reproduce the reentrant circuits of induced ventricular tachycardia (VT) in a porcine model of myocardial infarction (MI). Background Delayed-enhancement MRI has been used to characterize MI and “gray zones”, which are thought to reflect heterogeneous regions of viable and non-viable myocytes. Methods MI by coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…Previous efforts in modelling of infarcted hearts have been limited to 2D representations [46] or lacked full characterization of the entire ventricles including specific fiber orientations [47]. The individualized infarcted canine ventricular model used in this study incorporated accurate geometry, infarct distribution, and fiber orientation obtained from high resolution ex-vivo MRI and DTMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts in modelling of infarcted hearts have been limited to 2D representations [46] or lacked full characterization of the entire ventricles including specific fiber orientations [47]. The individualized infarcted canine ventricular model used in this study incorporated accurate geometry, infarct distribution, and fiber orientation obtained from high resolution ex-vivo MRI and DTMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the remote post-MI data, they demonstrated that infarct size at CMR, used in addition to LVEF, optimized arrhythmia risk prediction. Another potential utility of CMR is a technique of virtual EPS, described recently by Ng et al 101 in a porcine post-MI model. In this study, delayed-gadoliniumenhancement CMR images were used to create high-resolution 3-dimensional reconstructions of the LV.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…Další možnost případného využití CMR představuje metoda virtuální EPS, kterou nedávno popsali Ng a spol. 101 u prasečího modelu po IM. V jejich studii byly CMR obrazy s pozdním zesílením kontrastu gadolinia použity k trojrozměrným rekonstrukcím (s vysokým rozlišením) LK.…”
Section: Metody Stratifi Kace Rizika V čAsné Primární Prevenci Nssunclassified
“…Zhu et al [138] showed that models of the heart can be used to carry out non-invasive localization of accessory pathways in patients with Wolff-Parkinson-White syndrome. Ng et al [87] demonstrated the feasibility of using simulations to predict VT circuits. Relan et al [99] used a hy-brid X-ray and MR environment to image a patient heart, which was further personalized with voltage measurements.…”
Section: Clinical Applications Of Simulation-based Arrhythmia Researchmentioning
confidence: 99%